A biomechanical comparison of the two- and four-hole side-plate dynamic hip screw in an osteoporotic composite femur model. (29th June 2017) - Rog, Dominik; Grigsby, Phillip; Hill, Zachary; Pinette, William; Inceoglu, Serkan; Zuckerman, Lee
Objectives: The objectives of this study were (1) to compare the axial and torsional stiffness of a dynamic hip screw with a two- and four-hole side-plate in a synthetic model of a healed and stable intertrochanteric femur fracture and (2) to evaluate the load to failure, as well as propensity to peri-implant fracture. Methods: Fourth-generation synthetic composite femur models, simulating osteoporotic bone, were implanted with 135° dynamic hip screws (DHS) with either a two- or four-hole side-plate with or without a stable intertrochanteric fracture. Specimens were cyclically loaded up to a nondestructive load to determine the axial and torsional stiffness. Constructs were then loaded to failure in axial compression emulating physiologic forces. Failure load and location of the peri-implant fractures were recorded. Results: Axial and torsional stiffness did not differ significantly between the two- and four-hole constructs in either model. Likewise, there was no significant difference in the load to failure. In the intact femurs, failure occurred either at the end of the plate at the distal screw or through the lag screw hole. Conclusion: The results of this study demonstrate that DHS constructs with a two- or four-hole side-plate are biomechanically comparable with regard to axial and torsional stiffness and load to failure in an osteoporotic composite femur model. In a healed intertrochanteric fracture model, a two-hole construct did not appear to be more prone to peri-implant fracture. To date, a biomechanical comparison of these two implants with regard to torsional forces has not been reported.